2012
DOI: 10.4102/sajhrm.v10i2.436
|View full text |Cite
|
Sign up to set email alerts
|

The languishment of employee commitment in the light of perceptions of fair treatment in the workplace

Abstract: Orientation: This article reports on the behaviours displayed by committed employees and the influence of perceptions of fair treatment in the workplace on employees’ commitment.Research purpose: The objective of the study was to identify organisational behaviours that are indicative of employee commitment and whether perceptions of fair treatment in the workplace influence employees’ commitment.Motivation for the study: Employees are emotionally attached to organisations and treating employees in a fair m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Coetzee & Jo-Anne [56] investigated the role of fair treatment on job satisfaction and employee commitment at some leading banks in South Africa and discovered that fair treatment in the workplace does have a significant effect on job satisfaction resulting in better employee commitment.…”
Section: Equal Treatmentmentioning
confidence: 99%
“…Coetzee & Jo-Anne [56] investigated the role of fair treatment on job satisfaction and employee commitment at some leading banks in South Africa and discovered that fair treatment in the workplace does have a significant effect on job satisfaction resulting in better employee commitment.…”
Section: Equal Treatmentmentioning
confidence: 99%
“…Opposingly, research performed by Coetzee and Schreuder (2010) reported that black managers seemed to have lower commitment levels compared to white managers. Coetzee and Botha (2012) reported that opposing findings on whether ethnicity affect organisational commitment that may be a result of differences in the conceptualisation of commitment.…”
Section: Demographics and Organisational Commitment Levelsmentioning
confidence: 99%
“…Employees begin to seek for alternative job opportunities once they feel that they are not treated fairly (Van Dyk & Coetzee, 2012). According to Coetzee and Botha (2012), fair treatment in the organisation includes giving workers autonomy, treating workers with respect, giving workers equal responsibility and having expectations of workers. The positive relationship between organisational commitment and equal employment opportunities as a critical HR management practices is dependent on perceived equity by employees (Peete, 2016, p. 23).…”
Section: The Relationship Between Organisational Commitment and Human Resource Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, take into account their interests and needs when organizing work to achieve organizational goals. It is up to the leaders to determine whether favorable conditions are created to form a high level of commitment and loyalty among employees in the organization when employees perceive those events that occur between them and their leaders as representatives of the organization as fair and attractive for themselves (Coetzee & Botha, 2012).…”
Section: Introductionmentioning
confidence: 99%